Testing ToF Sensors for Use in Obstacle Detection Systems - Grzegorz SZCZEPAŃSKI; Aliaksandra SHMYK (Problemy Mechatroniki)
ToF (Time of Flight) sensors have been gaining popularity in recent times as a cheap and accurate way to take distance measurements. They may prove to be a key component of obstacle detection systems in the near future. This paper presents a stepper motor system with two measurement modules containing ToF sensors. The results of distance measurements made with these modules relative to a flat surface for different sensor modes are presented. Standard deviations were determined for the measurement results and a polynomial fitting was performed using the linear least squares method. The results were used to select the sensor for further work in terms of its use in an obstacle detection system.